Female leadership and workplace climate - Sule Alan; Gozde Corekcioglu; Mustafa Kaba; Matthias Sutter (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
Using data from over 2,000 professionals in 24 large corporations, we show that female leaders shape the relational culture in the workplace differently than male leaders. Males form homophilic professional ties under male leadership, but female leadership disrupts this pattern, creating a less segregated workplace. Female leaders are more likely to establish professional support links with their subordinates. Under female leadership, female employees are less likely to quit their jobs but no more likely to get promoted. Our results suggest that increasing female presence in leadership positions may be an effective way to mitigate toxic relational culture in the workplace.
Keywords: C93; J16; M14; 330; female leadership; workplace climate; social networks